The lifeboat : a novel - Rogan, Charlotte (New York : Little, Brown and Co., 2012)
Forced into an overcrowded lifeboat after a mysterious explosion on their trans-Atlantic ocean liner, newly widowed Grace Winter battles the elements and her fellow survivors and remembers her husband, Henry, who set his own safety aside to ensure Grace's.
"A Reagan Arthur book."
Keywords: Shipwreck survival -- Fiction; Young women -- Fiction; Ocean liners -- Fiction; Psychological fiction